Застосування методу експериментального мутагенезу для овочевої кукурудзи - Куліш, О.Ю.; Погреблюк, М.В.; Ковальчук, З.В.; Бабич, В.О.; Парій, Я.Ф.; Симоненко, Ю.В.; Парій, М.Ф. (Фактори експериментальної еволюції організмів, 2016)
Aim. Mutation is the expansion of the genetic diversity of corn, which is the original material selection in the practice of this culture. The purpose of our work was getting lines of vegetable maize with genetic mutations, which can be used to improve the properties of vegetable corn, using chemical mutagens. Methods. In the research used a line of corn PА-3 and samples 727 G, 708 A, 308 E A, B, 725. As a mutagen applied 5-bromuracil in 0.0191, 0.0955, 0.191, 0.573 and 1.91 g/l, respectively, and sodium ozidum (NaN3 ) – 1.95, 2.6 and 3.25 g/l. Results. It was obtained a new mutant line of vegetable corn and it is characterized by complex economic and valuable features. Conclusions. We received a new subspecies of the vegetable corn, which is promising for further research and production as a new generation of baby corn. Keywords: Vegetable maize/corn, mutagenesis, mutations, baby corn.